Phylogenetic analysis of the SARS-CoV-2 virus gene-based on the chain A glycoprotein spike in Wuhan - Pakpahan, Suyarta Efrida; Sari, Ira Prima; Koesmawati, Dea (Asian Journal of Health and Applied Sciences, 2022)
The spread of COVID-19 in various countries has increased the death toll due to COVID-19. Spike glycoproteins of the SARS-CoV-2 virus have an important role in binding to host cell receptors. This spike can identify the SARS-CoV-2 kinship in Wuhan and other countries by phylogenetic analysis. This study aims to determine the phylogenetic relationship of COVID-19 from Wuhan with the other countries obtained from the NCBI Gene bank based on spike chain A glycoproteins. The method uses NCBI's BLAST program to search for similar sequences, ClustalW's program to perform multiple alignment sequencing, and MegaX to create a phylogenetic tree. The research results Spike glycoprotein chain A in Wuhan has the closest kinship with the United States. This is indicated by the formation of tree branches close to each other but still in the same group as spike glycoproteins in other countries. Phylogenetic tree validated by the bootstrap test that value of 100%, which means it shows the sturdiness of the tree can be trusted. The conclusion is there is no significant difference in the characteristics of spike glycoprotein chain A, as for some countries that have spike amino acid differences in glycoprotein chain A, such as Pakistan, Poland, and Wuhan. The amino acid difference is considered normal because the virus will continue to evolve in order to adapt to the environment